Cyclisation versus 1, 1‐Carboboration: Reactions of B(C6F5)3 with Propargyl Amides. Issue 36 (6th August 2013) - Melen, Rebecca L.; Hansmann, Max M.; Lough, Alan J.; Hashmi, A. Stephen K.; Stephan, Douglas W.
Abstract A series of propargyl amides were prepared and their reactions with the Lewis acidic compound B(C6F5)3 were investigated. These reactions were shown to afford novel heterocycles under mild conditions. The reaction of a variety of N‐substituted propargyl amides with B(C6F5)3 led to an intramolecular oxo‐boration cyclisation reaction, which afforded the 5‐alkylidene‐4, 5‐dihydrooxazolium borate species. Secondary propargyl amides gave oxazoles in B(C6F5)3 mediated (catalytic) cyclisation reactions. In the special case of disubstitution adjacent to the nitrogen atom, 1, 1‐carboboration is favoured as a result of the increased steric hindrance (1, 3‐allylic strain) in the 5‐alkylidene‐4, 5‐dihydrooxazolium borate species.